An Exploratory Study of Discipline in Primary Classroom: Some Reflections and Experiences from the Field - Major, Shama Norien; Mittal, Surbhi (Voices of Teachers and Teacher Educators, 2023)
This paper is an attempt to reflect some of the observations on discipline in primary classrooms of government schools in Delhi. The qualitative data was analysed in the light of the theoretical lens of psychologists, theorists and educators. It was found that certain rules are imposed on children to be followed in order to regulate their behavior during classroom processes and the teachers act as an authoritative figure to maintain a strict level of discipline in the classroom by treating children as inactive beings. A child who disobeys the rules had to face some kind of penalisation as a consequence of misbehavior. The teacher uses different strategies both implicitly and explicitly to regulate the behavior of children. The teacher considers children to behave as passive beings who should work silently during the classroom processes. Students who display any form of behavior which goes against the prescribed rules of the classroom were highly disapproved and discouraged by the teachers. In the name of "discipline children are expected to refrain from indulging in any form of activities which are required as their basic needs of survival. The study reveals that discipline is perceived as a process to control the physical mobility of children, maintaining silence and maintaining physical order. This paper suggests that effective classroom management is not possible without discipline, and the teacher plays a crucial role in inculcating the value of discipline; not just to achieve immediate goals but also long-term aims of education which emphasises self-discipline among children. Teacher education programs should improve the quality of teacher education in bridge the gap between the educational theories and praxis which are used to discipline children for effective classroom management.